(3JSgjd GdefGaY aj GdWH hGdMceIs - (3EHQGgje Hf YHO GdQMef Hf CHj HcQ GdCRQbj Gdjefj,J (B815 (3g` s
(3ChdgG (B:s
(3hHYO aEf GdWH YXje faYI hbOQg hYdG TQag haNQg eGTJgQ PcQg haVdg s
(3BNQgG (B:s
(3eHJhQ GdBNQ , JfJgi HaUd ajeG jcJH dYSQ GdhdGOI (B((3Gi fMh KdKi GdeWHhY(B) s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B44s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdChd (B- (3U (B47 s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHg hdi GdOjf (B(2489) s
Keywords: (3GdWHs